On some Abelian p-groups and their capability - Zainal, Rosita (2015)
A group is said to be capable if it is a central factor group; equivalently, if and only if a group is isomorphic to the inner automorphism group of another group. In this research, the capability of some abelian pgroups which are groups of order p4 and p5, where p is an odd prime are determined. The capability of the groups is determined by using the classifications of the groups.